Gaspar de Villaroel, OSA : un ilustre prelado americano, un clásico del derecho indiano (1587-1665) - Martínez Gutiérrez, Gregorio (Valladolid Estudio Agustiniano, 1994)
"Traces life of the Spanish cleric from childhood to position as Archbishop of Charcas. More descriptive than analytical. Based mainly on secondary sources"--Handbook of Latin American Studies, v. 58.
Keywords: Villarroel, Gaspar de, -- approximately 1587-1665.; Augustinians -- South America -- Biography; Catholic Church -- South America -- Bishops -- Biography; #GOSA:XX.III.D.Villa.M; South America -- Church history -- 17th century